Polyamide reverse osmosis composite membrane and preparation method thereof - THE INVENTOR HAS WAIVED THE RIGHT TO BE MENTIONED (2018)
The invention discloses a preparation method of a polyamide reverse osmosis composite membrane. The preparation method includes providing of polyamine water-phase solution and performing of interfacial polymerization reaction, wherein polyether modified polydimethylsiloxane in concentration of 0.01wt%-2wt% is dissolved in the polyamine water-phase solution. The invention further provides the polyamide reverse osmosis composite membrane prepared according to the preparation method. In the preparation method, polyether modified polydimethylsiloxane serving as a surfactant is applied to preparation of the reverse osmosis composite membrane, has unique advantages as the surfactant due to low surface tension and long flexible side chains and enables increasing of the salt removing rate of the polyamide reverse osmosis composite membrane with low water flux influences. 本发明公开了种聚酰胺反渗透复合膜的制备方法，包括提供多元胺水相溶液，所述多元胺水相溶液中溶解有聚醚改性聚二甲基硅氧烷，所述聚醚改性聚二甲基硅氧烷的浓度为0.01wt％-2wt％，还包括进行界面聚合反应。本发明还提供采用上述方法制备的聚酰胺反渗透复合膜。本发明的制备方法中，将聚醚改性聚二甲基硅氧烷